Research on VoIP Acoustic Echo Cancelation Algorithm Based on Speex - Liu hua-zhu; Zhao xiao-fang; Lin sheng-xin (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
Echo cancellation has been a major problem to be solved in VoIP, although the integrated echo cancellation module in Speex, it does not consider thread synchronization issues. The frequency domain echo cancellation algorithm MDF of speex is analyzed, and then a synchronization method of playing thread and recording thread is proposed. The results show that the acoustic echo canceller which achieved by the proposed method meet the requirements of voice communication, implementation is easier and therefore provides a reference for the VoIP voice communication and mobile communication terminal.